Methodology For the Definition and Application of Motivational Strategies in A Basketball Academy - Sánchez M; García B (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Understanding motivation as a means to achieve learning (Martín, 2020), it is important to consider that educational projects must define a series of strategies and actions with the aim of achieving emotional states that favour the acquisition of learning objectives. To this end, a practical experience is presented to define and apply motivational strategies in a basketball school. To evaluate the experience, the Spanish version of (MURCIA, COLL, GARZÓN, & ROJAS, 2008) of the Basic Psychological Needs in Exercise Scale (BPNES) and the Spanish version of Cecchini, González, Prado, and Brustad (2005) of the questionnaire on the perception of the motivational climate in sport-2 are used. In addition to proposing a methodology to define and apply motivational strategies, the evaluation carried out shows that the athletes participating in the experience have a high feeling of competence and sense of belonging to the group and that the motivational climate where the experience has been developed is oriented towards improvement. These data mark a positive trend towards adherence to sport, persistence, the pleasant experience of sport and constitute an ideal framework for learning.